The Light-Time Effect in SZ Lyn - Gazeas, K. D.; Niarchos, P. G. (The Light-Time Effect in Astrophysics: Causes and cures of the O-C diagram, 2005)
New CCD observations of the pulsating star SZ Lyn are analyzed and a new ephemeris is proposed. The photometric data collected over the last 43 years are used to determine and update the pulsational and orbital elements, based on the light-time effect detected in the O-C diagram.